Pilot Program to Improve Self-Management of Patients with Heart Failure by Redesigning Care Coordination. (23rd April 2014) - Shaw, Jessica D.; O'Neal, Daniel J.; Siddharthan, Kris; Neugaard, Britta I.
Abstract : Objectives . We tested both an educational and a care coordination element of health care to examine if better disease-specific knowledge leads to successful self-management of heart failure (HF). Background . The high utilization of health care resources and poor patient outcomes associated with HF justify tests of change to improve self-management of HF. Methods . This prospective study tested two components of the Chronic Care Model (clinical information systems and self-management support) to improve outcomes in the self-management of HF among patients who received intensive education and care coordination during their acute care stay. A postdischarge follow-up phone call assessed their knowledge of HF self-management compared to usual care patients. Results . There were 20 patients each in the intervention and usual care groups. Intervention patients were more likely to have a scale at home, write down their weight, and practice new or different health behaviors. Conclusion . Patients receiving more intensive education knew more about their disease and were better able to self-manage their weight compared to patients receiving standard care.